Characterizing the binding of TC-5619 and encenicline on the alpha7 nicotinic acetylcholine receptor using PET imaging in the pig - Magnussen, Janus H.; Ettrup, Anders; Lehel, Szabolcs; Peters, Dan; Dyssegaard, Agnete; Thomsen, Morten S.; Mikkelsen, Jens D.; Knudsen, Gitte M. (Frontiers in Neuroimaging, 2024)
The alpha7 nicotinic acetylcholine receptor (α7-nAChR) has has long been considered a promising therapeutic target for addressing cognitive impairments associated with a spectrum of neurological and psychiatric disorders, including Alzheimer's disease and schizophrenia. However, despite this potential, clinical trials employing α7-nAChR (partial) agonists such as TC-5619 and encenicline (EVP-6124) have fallen short in demonstrating sufficient efficacy. We here investigate the target engagement of TC-5619 and encenicline in the pig brain by use of the α7-nAChR radioligand 11C-NS14492 to characterize binding both with in vitro autoradiography and in vivo occupancy using positron emission tomography (PET). In vitro autoradiography demonstrates significant concentration-dependent binding of 11C-NS14492, and both TC-5619 and encenicline can block this binding. Of particular significance, our in vivo investigations demonstrate that TC-5619 achieves substantial α7-nAChR occupancy, effectively blocking approximately 40% of α7-nAChR binding, whereas encenicline exhibits more limited α7-nAChR occupancy. This study underscores the importance of preclinical PET imaging and target engagement analysis in informing clinical trial strategies, including dosing decisions.